Data engineers vs. data scientists : how misconceptions of data roles can hurt teams and compromise productivity - Anderson, Jesse (O'Reilly Media, 2019)
Data engineers and data scientists are not interchangeable--and misperceptions of their roles can hurt teams and compromise productivity. This article clears up the differences of each role and how to best optimize these roles.